Voltammetric behaviour of oligonucleotide lipoplexes adsorbed onto glassy carbon electrodes - Piedade, J. A. P. (2004)
The voltammetric behaviour of oligonucleotide lipoplexes (ODN-lipoplexes) prepared from short oligodeoxynucleotides (ODN), with different base compositions, and liposomes of the cationic lipid DOTAP, was studied by differential pulse voltammetry with a glassy carbon mini-electrode. It was found that the ODN base composition influences the ODN-lipoplex voltammetric response. Differential pulse voltammograms for ODN-lipoplexes of the ODN adenosine nucleotides present two different features when compared with the differential pulse voltammograms obtained for free ODN: a new peak appeared and the peak attributed to oxidation of adenosine diminished or was absent, depending on whether the ODN sequence had guanosine nucleotides or not. The presence of guanosine nucleotides in the ODN-lipoplex led to a peak due to guanosine oxidation with similar potential and current to the peak obtained for guanosine oxidation in free ODN. No detectable peaks were recorded in the voltammograms obtained with lipoplexes composed of ODN containing only pyrimidine bases. It was possible to show by voltammetry the occurrence of partial denaturation of short double helices of ODN when mixed with DOTAP liposomes to generate lipoplexes. The extent of denaturation was observed to increase with lipoplex (+/-) charge ratio as shown by the increase in the differential pulse voltammetry peak currents. The electrochemical characterisation of lipoplex properties at a charged interface can be important for understanding and development of these gene therapy vectors.